Ruch niepodległościowy w Katalonii i jego znaczenie dla Katalończyków w drugiej dekadzie XXI wieku (Studia Iberystyczne, 2021)
Independence Movement in Catalonia and Its Significance for Catalans in the Second Decade of the 21st CenturyThe paper focuses on the issues of the independence movement in Catalonia in the second decade of the 21st century. The aim of this study is to explore the evolution of Catalonia’s separatist aspirations in this period in terms of politics and especially society, and thus the position of Catalans towards this phenomenon. A significant element of the author’s considerations is the demonstration and analysis of the specificity and factors determining contemporary Catalan separatism, as well as concerning the context of perceiving Catalans as a nation. The independence process in the second decade of the 21st century, including treatment of events such as the judgment of the Spanish Constitutional Court in 2010, the independence referendum in 2017, or the trial and judgment of Catalan politicians in 2019, taken into account by the author, hold considerable importance for this work. The key part of the paper is to present the issues of the independence movement in the discussed period in terms of society; its emerging role in the Catalan society, and the impact of the activities and actions of Catalans themselves on the politics and development of the region’s separatist aspirations.